Analysis of the influence of tax knowledge and tax compliance on the perception of tax revenue among MSME actors in Cibungbulang District at KPP Pratama Ciawi - Nurmalasari Nurmalasari; Mahwiyah Mahwiyah (Priviet Social Sciences Journal, 2026)
This study examines how tax understanding and taxpayer compliance contribute to improving regional tax revenue among micro, small, and medium enterprises registered at a local tax office. This study adopts a quantitative approach supported by survey responses from business actors actively engaged in fulfilling their tax obligations. The analysis highlights that a higher level of tax understanding encourages taxpayers to perform their administrative duties more accurately, creating a stronger awareness of legal responsibilities and the role of taxation in regional development. Although taxpayer compliance varies across respondents, the combined influence of both variables has meaningful implications for strengthening the effectiveness of local tax collection. The findings emphasize the importance of continuous socialization, targeted guidance programs, and enhanced tax literacy to ensure that business actors are better equipped to meet regulatory requirements. This study contributes to the growing discourse on taxpayer behavior and regional fiscal capacity.